Temporal variation of the stress field during the construction of the central Andes: Constrains from the volcanic arc region (22–26°S), Western Cordillera, Chile, during the last 20 Ma - Giambiagi, Laura Beatriz (2016)
In order to understand the response of the stress field state to intrinsic processes during the construction of the Andes, such as thickening of the continental crust, lithospheric delamination, and/or thermal weakening, we investigate the stress field evolution of the arc region since the last 20 Myr, in the central Andes (22–26.5°S). The 43 reduced paleostress tensors derived from inversion of 682 fault slip data reveal a complex pattern of stress states during the last episode of orogenic construction and topographic uplift. We identify two geodynamic stages: the first stage corresponds to the construction of the Altiplano/Puna plateau and the second one to its gravitational collapse. Four stress states that have prevailed in the Altiplano/Puna plateau since middle Miocene times characterize the transition from one stage to the other. Along the study latitudes, a spatiotemporal change in stress state is clearly observed, which led to an understanding that a change in the stress field may be related not only to the boundary conditions but also to intrinsic factors associated with the construction of the Andean orogeny. Our results suggest that approximately at 13–10 Ma and approximately 8–5 Ma, in the southern Altiplano and northern Puna, and in the southern Puna, respectively, regional elevation and crustal thicknesses reached threshold values necessary to generate the orogenic collapse.